Pelatihan Unit Kompetensi Mengoperasikan PLC SKKNI 631 Tahun 2016 untuk Guru Mekatronika SMK Negeri 10 Bekasi - Eka Samsul Maarif; Budiyanto; Husnibes Muchtar; Machbubul W (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
One of the increasing needs for automation in the industrial world is the impact on the supply of skilled workers who are able to operate industrial automation systems, especially PLC-based systems. So that SMK as a formal educational institution must be able to meet this demand. The Community Service Program is carried out at SMK N 10 Bekasi in the form of training according to the Competency Unit to Operate PLCs to equip teachers to have competencies in accordance with the applicable SKKNI, in order the teachers can teach by referring to these standards. The results of the pre-test showed that the initial conditions of the 3 teachers had very good skills in understanding the work process flow of the automation system, being able to read wiring diagrams, being able to make installation connections on the PLC according to the drawings, being able to operate the PLC and being able to test the system. However, the quality of the cable and the installation of terminals still has many errors. The results of the post test showed that the training was able to reduce the average number of errors from 15 to 5.33 or decrease 64.46% and reduce the average installation time of connecting cables from 73.66 to 53.55 or decrease 27.3%.